From which soil metal fractions Fe, Mn, Zn and Cu are taken up by olive trees (Olea europaea L., cv. 'Chondrolia Chalkidikis') in organic groves?. (1st December 2017) - Chatzistathis, T.; Papaioannou, A.; Gasparatos, D.; Molassiotis, A.
Abstract: Organic farming has been proposed as an alternative agricultural system to help solve environmental problems, like the sustainable management of soil micronutrients, without inputs of chemical fertilizers. The purposes of this study were: i) to assess Fe, Mn, Zn and Cu bioavailability through the determination of sequentially extracted chemical forms (fractions) and their correlation with foliar micronutrient concentrations in mature organic olive (cv. 'Chondrolia Chalkidikis') groves; ii) to determine the soil depth and the available forms (fractions) by which the 4 metals are taken up by olive trees. DTPA extractable (from the soil layers 0–20, 20–40 and 40–60 cm) and foliar micronutrient concentrations were determined in two organic olive groves. Using the Tessier fractionation, five fractions, for all the metals, were found: exchangeable, bound to carbonates (acid–soluble), bound to Fe-Mn oxides (reducible), organic (oxidizable), as well as residual form. Our results indicated that Fe was taken up by the olive trees as organic complex, mainly from the soil layer 40–60 cm. Manganese was taken up from the exchangeable fraction (0–20 cm); Zinc was taken up as organic complex from the layers 0–20 and 40–60 cm, as well as in the exchangeable form from the upper 20 cm. Copper was taken up from the soil layers 0–20 and 40–60 cm as soluble organic complex, and as exchangeable ion from the upper 20 cm. Our data reveal the crucial role of organic matter to sustain metal (Fe, Zn and Cu) uptake -as soluble complexes-by olive trees, in mature organic groves grown on calcareous soils; it is also expected that these data will constitute a thorough insight and useful tool towards a successful nutrient and organic C management for organic olive groves, since no serious nutritional deficiencies were found. Graphical abstract: Principal component analysis of soil metal fractions in different depths suggested covariations with soil properties in organic olive groves. This graph demonstrates that the accumulation of organic matter in surface soils (0–20 cm) controls the bioavailability of Fe, Mn, Zn and Cu whether estimated on the basis of a single extraction (DTPA) or based on the labile fractions of a sequential extraction scheme. Highlights: Soil metal fractions were studied in two organic olive groves. Fe, Mn, Zn and Cu were taken up by trees as exchangeable ions and organic complexes. Most foliar nutrient concentrations were within the optimum range of sufficiency. Maintenance of soil organic matter is crucial to sustain metal uptake.